Chapter Qualitative and Quantitative Assessment of Fatty Acids of Hazelnut by GC-TOF/MS - Ding, Jian (InTechOpen, 2018)
On the basis of gas chromatography coupled with time-of-flight mass spectrometry, we assessed the constituents and relative quantities of fatty acids extracted by supercritical carbon dioxide in seeds of hazelnut. Hazelnut seeds contain four fatty acids (palmitic, stearic, oleic, and linoleic acids). The content of unsaturated fatty acids is more than 92.9% in hazelnut seed oil. Oleic acid, which constitutes 76.1%, has a high boiling point and low volatility. Hazelnut oil has good storage stability and is recommended as senior edible oil for health and the food industry. Our study reveals the important contribution of hazelnut in the production of bioactive oils and compounds that prevent obesity, cancer, coronary disease, and many other human health as well as pharmaceutical challenges.